An analysis of Daniel Kahneman's Thinking, fast and slow - Allan, Jacqueline Anne (Macat International Ltd., 2017)
Thinking, Fast and Slow by Daniel Kahneman offers a general audience access to over six decades of insight and expertise from a Nobel Laureate in an accessible and interesting way. Kahneman's work focuses largely on the problem of how we think, and warns of the dangers of trusting to intuition - which springs from "fast" but broad and emotional thinking - rather than engaging in the slower, harder, but surer thinking that stems from logical, deliberate decision-making. Written in a lively style that engages readers in the experiments for which Kahneman won the Nobel, Thinking, Fast and Slow's real triumph is to force us to think about our own thinking.